(untitled) (Tanzania Medical Journal, 2020)
Background: The WHO estimates that approximately 600 million people fall ill after consumption of contaminated food and over 420 000 die every year, resulting in loss of 33 million healthy life years. Hand hygiene is considered by the WHO to be the most effective preventive measure for infectious diseases including food borne diseases. Methods: A laboratory-based study involving convenient sampling of common brands alcohol based hand sanitizers (ABHS) from retail community pharmacies and local supermarkets was conducted in Ilala District, Dar es salaam, Tanzania The study was conducted , between December 2017 to January 2018. A modified protocol of The European Norm (EN) 1500 was used for in vivo testing of sampled ABHs. Efficacy was evaluated using standard strain of Escherichia coli. A total of 26 healthy volunteers were used for hand sanitization. The percentage of bioburden/microbial reduction was assessed at baseline and after treatment, and the log reduction factor calculated. Results: A total of 10 gel ABHS were purchased and assayed for antibacterial efficacy. Majority (70%) of ABHS were imported products and contained ethanol as the sole active ingredient. About 60% of them did not correctly indicate the label disclosure information on concentration of active ingredients. Only one product was efficacious against E.coli with log reduction of 3.75; while majority (70%) of the samples had poor bacterial efficacy with log reduction ranging from 0.140 -0.664. Conclusions: Most of ABHS gel products available in the Dar es Salaam market were not efficacious as per FDA and EN 1500 guidelines. Post market surveillance is recommended of the circulating ABH to safe guard consumers. Keywords: Hand sanitizers, efficacy, E.coli, EN 1500